Public administration of cross-sectoral interaction in the field of mental health: an experimental project of advanced training for military psychologists at civilian higher education institutions - Vasylkovskyi, Oleksandr; Bilokon, Mykhailo (Theory and Practice of Public Administration, 2026)
The article examines the issues of public administration of the mental health care system in the context of prolonged armed aggression. It is emphasized that the growing need for psychological assistance among military personnel and the civilian population has led to a staff shortage that objectively cannot be overcome solely by traditional methods of closed military education. The purpose of the study is a comprehensive analysis of the latest public management mechanisms for implementing the government experimental project on the advanced training of military psychologists at civilian higher education institutions. The authors demonstrate the undeniable management advantage of transitioning from a formal nomenclature model to a functional model of staffing in crisis conditions. Involving the intellectual potential of civilian higher education allows the state to quickly deploy intensive modular programs, practically implementing the global strategy of rational task-sharing. This adaptive approach provides both the front line and the rear with the necessary number of certified specialists capable of providing quality psychosocial assistance and performing timely screening. Particular attention in the study is paid to the institutionalization of care for the service providers themselves. It is proven that the regulatory consolidation of mandatory supervision and the development of effective systems for preventing professional burnout are important tools for preserving the core staff of the field. In conclusion, it is substantiated that flexible cross-sectoral interaction and large-scale digitalization of human resource management form a single resilient national mental health space, laying a solid foundation for the post-war recovery of the nation.